ISLAMOFOBIA DI PRANCIS: DISKRIMINASI PEREMPUAN MUSLIM MAGHRIBI - Petsy Jessy Ismoyo (Universitas Kristen Satya Wacana, 2016)
France is a country with the largest Moeslem population in Europe, nearly 7,5% of thepopulation are Moeslems. Ironically, radicalization has increased in the past 10 years. Itaffects the rise of Islamophobia and it continues to increase until 2015. The worst effectsof Islamophobia experienced by Moeslems Maghribi Women in France.This paper tries to show the relation between identity, Islamic context, anddiscrimination. The author tries to analyze the cause and impact of the discrimination tothe identity of Moeslem Maghribi Women. Discrimination is focused on the difficulties tofind a job. This paper is using qualitative method with literature study, and Theory ofIdentity by Stuart Hall.The result is expected to give an overview of multiculturalism, Islamophobia, anddiscrimination against Moeslem Maghribi Women in France in order to defend the rightsand freedom of the Moeslem Maghribi Women. The results also gives recommendation tothe related parties, such as: government, French institutions, and media.Keywords: Multiculturalism in France, Islamophobia, Identity, Discrimination, Women,Immigrant, Moeslem, Maghribi